2021
DOI: 10.3390/children8050345
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Wellbeing at Schools: Health Promotion in Primary Schools with the Use of Digital Methods

Abstract: Mental health disorders among primary school children remain a crucial issue. Early health promotion interventions can positively affect and prevent the onset of mental disorders. Promising digital mental health methods have been implemented for adolescents and youths with scarce evidence among younger ages. Therefore, the aim of the current systematic review was to identify health promotion interventions on mental health and wellbeing, with the use of digital methods, delivered in primary school settings. Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
2
5
0
6
Order By: Relevance
“…Nevertheless, The attitude of solidarity in mental health issues is more related to Vision 1 and to the salutogenic approach. Consistent with our findings related to the other necessary changes at this level, Sakellari et al (2021) reported promising results in their study concerning the use of digital interventions in mental health issues in school settings. The need for an improvement in competence in mental health issues has also been reported earlier (see for example Gee et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Nevertheless, The attitude of solidarity in mental health issues is more related to Vision 1 and to the salutogenic approach. Consistent with our findings related to the other necessary changes at this level, Sakellari et al (2021) reported promising results in their study concerning the use of digital interventions in mental health issues in school settings. The need for an improvement in competence in mental health issues has also been reported earlier (see for example Gee et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, health promotion is a cornerstone in the profession of SNs (WHO, 2021a), and the focus on mental health issues should be in promotion, prevention and early interventions, according to the political strategies and guidelines (Vorma et al, 2020, WHO, 2021b). According to earlier research, promotive interventions are beneficial (O'Connor et al, 2017; Sakellari et al, 2021) and preventive interventions cost‐effective (Feldman et al, 2020; Vartiainen et al, 2021). The results of our study tend to indicate that these interventions are underused.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also confirms some of the features of effective methods documented in the literature (Langford et al, 2014;Shackleton et al, 2016), including the use of digital technology (Sakellari et al, 2021), for mental health promotion. These include a commitment to inclusivity and the multidimensionality in interventions, and a focus on facilitators' competence (Shackleton et al, 2016).…”
Section: Discussionsupporting
confidence: 83%